2016
DOI: 10.1002/mawe.201600617
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue assessment of high strength leaf springs based on the FKM guideline

Abstract: Analytical fatigue strength calculations based on the FKM guideline have been performed for hot tapered and stress‐shot‐peened high‐strength leaf spring specimens subjected to three‐point fatigue bending. The ultimate tensile strength of the decarburized specimens' surface has been approached by means of Rockwell‐C hardness measurements, and used as input for the approximation of its fatigue limit and mean stress sensitivity. Surface roughness and residual stress measurements were performed to take account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Fatigue tests are performed on 3-point bending test rigs using a servo hydraulic actuator [6], figure 4. The leaf spring is clamped in the centre with steel blocks that connect to the actuator.…”
Section: Testingmentioning
confidence: 99%
“…Fatigue tests are performed on 3-point bending test rigs using a servo hydraulic actuator [6], figure 4. The leaf spring is clamped in the centre with steel blocks that connect to the actuator.…”
Section: Testingmentioning
confidence: 99%
“…By using this technique, a compressive residual stress field appears in the surrounding elastically deformed material. Pyttel et al and Giannakis and Savaidis have calculated analytically fatigue strength based on the "fracture mechanics proof of strength for engineering components" guideline for stress shot-peened high-strength leaf spring samples NOMENCLATURE: a, Crack length; D, Hole diameter; R, Load ratio; S11, Crack opening stresses; W, Specimen width; da dN , Fatigue crack growth rate; σ global , Global stress applied on the geometry; σ local , Maximum stress around the hole; ΔK, Stress intensity factor range; ΔP, Applied fatigue load range under a 3-point bending fatigue test 7,8 and found that the fatigue life was improved due to peening. For example, Donzella et al have studied the effect of shot peening on mechanical properties, material microstructure, and residual stress profile in sintered steel plates.…”
Section: Introductionmentioning
confidence: 99%
“…5 Gan et al have investigated the effect of shot peening on a T-welded structure made of Q345D steel 6 and found that the suitable peening intensity could improve fatigue life compared with an unpeened structure. Pyttel et al and Giannakis and Savaidis have calculated analytically fatigue strength based on the "fracture mechanics proof of strength for engineering components" guideline for stress shot-peened high-strength leaf spring samples NOMENCLATURE: a, Crack length; D, Hole diameter; R, Load ratio; S11, Crack opening stresses; W, Specimen width; da dN , Fatigue crack growth rate; σ global , Global stress applied on the geometry; σ local , Maximum stress around the hole; ΔK, Stress intensity factor range; ΔP, Applied fatigue load range under a 3-point bending fatigue test 7,8 and found that the fatigue life was improved due to peening. Mahmoudi et al studied the effect of initial compressive residual stress on subsequent compressive residual stress induced by shot peening and found that the initial residual stress was wiped out by shot peening up to the maximum compressive residual stress point.…”
Section: Introductionmentioning
confidence: 99%